Immune-Therapy-Related Toxicity Events and Dramatic Remission After a Single Dose of Pembrolizumab Treatment in Metastatic Thymoma: A Case Report - Shen, Li; Chen, Haiyan; Wei, Qichun (Frontiers in Immunology, 2021)
Immune checkpoint inhibitor therapy has become a promising option for the treatment of late-stage thymic epithelial tumors. In this manuscript, we presented a patient with metastatic thymoma administrated of anti-programmed cell death protein 1 (PD-1) antibody pembrolizumab. Although the patient underwent a rapid and dramatic response to one dose of pembrolizumab, she suffered a storm of immune-therapy related toxicity events (irAEs), including liver and kidney dysfunction, hypothyroidism and myocarditis. We didn’t observe >grade 3 irAEs, and proceed with pembrolizumab therapy after the function recovered. Although no guidelines recommend dose reduction of immunotherapy re-treating following initial irAEs, we optimise dose of pembrolizumab to minimize the irAEs induced by PD-1 antibody while maintaining clinical effectiveness. Excitingly, we observe remarkable tumor remission and mild toxicities of half dose of pembrolizumab in this case. In conclusion, the clinical utilization of immunotherapy is an encouraging therapeutic alternative for advanced thymomas. At the same time, patients have to be monitored very carefully, because of the risk to develop irAEs.